2023
DOI: 10.3390/molecules28135016
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Sensory Characterization of Xinomavro Red Wine Using Grapes from Protected Designations of Northern Greece

Abstract: Despite Xinomavro (Vitis vinifera L.) being a well-known noble red grape variety of northern Greece, little is known about its ‘‘bouquet’’ typicity. Volatile compounds of Xinomavro wines produced using a common vinification protocol were analyzed by gas chromatography–mass spectrometry and sensory descriptive analysis was carried out with a trained panel. Wines were characterized by the presence of fatty acids, ethyl and acetate esters, and alcohols, with contributions from terpenes and a volatile phenol. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Although the contributions of grapes to the production of esters from fermentation is not entirely explained, Ferreira et al [53] have demonstrated that esters might impact the varietal odor of young red wines. Ethyl hexanoate and ethyl octanoate were found to provide a fruity scent to the wines elsewhere [48]. The highest concentration of both VCs was reported in Xinomavro of Goumenissa at 4.19 and 7.38 mg/L, respectively.…”
Section: Vcs Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…Although the contributions of grapes to the production of esters from fermentation is not entirely explained, Ferreira et al [53] have demonstrated that esters might impact the varietal odor of young red wines. Ethyl hexanoate and ethyl octanoate were found to provide a fruity scent to the wines elsewhere [48]. The highest concentration of both VCs was reported in Xinomavro of Goumenissa at 4.19 and 7.38 mg/L, respectively.…”
Section: Vcs Analysismentioning
confidence: 97%
“…This indicates that PEF treatment may influence the concentration of key components that contribute to the aromatic profile of the wines. In a study by Goulioti et al [48], six Xinomavro wines were analyzed for their volatile compounds. 2-Phenylethanol was found in considerably higher amounts than in our samples as it was measured at 35.1-53.3 mg/L.…”
Section: Vcs Analysismentioning
confidence: 99%